2009
DOI: 10.1002/bjs.6686
|View full text |Cite
|
Sign up to set email alerts
|

Safety of extended endoscopic mucosal resection and endoscopic submucosal dissection following the Japanese Gastric Cancer Association treatment guidelines

Abstract: Extending the indications for EMR and ESD according to the Japanese Gastric Cancer Association guidelines carries an increased risk of lymph node metastasis. For cancers meeting these criteria, treatment by gastric resection with lymph node dissection should still be considered. A well differentiated mucosal cancer of any size without ulceration may be considered as an extended indication for EMR or ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 25 publications
(24 reference statements)
2
44
1
Order By: Relevance
“…A more advanced technique, endoscopic submucosal dissection, has been developed to facilitate the successful removal of larger and deeper tumors than those that can be removed via endoscopic mucosal resection. This technique has been widely used as an alternative to surgery for the treatment of differentiated-type EGC with specific indications in Asian countries, including Korea and Japan [2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…A more advanced technique, endoscopic submucosal dissection, has been developed to facilitate the successful removal of larger and deeper tumors than those that can be removed via endoscopic mucosal resection. This technique has been widely used as an alternative to surgery for the treatment of differentiated-type EGC with specific indications in Asian countries, including Korea and Japan [2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these fi ndings, it was suggested that the criteria for EMR and ESD as local treatment for EGC should be extended [ 9 -13 ]. According to a recent study of patients who had surgery for EGC at Seoul National University Bundang Hospital [ 14 ], of 132 patients with mucosal cancers, 129 met the extended indications for EMR or ESD while three (2.3 %) had lymph node metastasis. Of the 52 submucosal cancer cases that met the extended indications for EMR or ESD, two (4 %) had lymph node metastasis.…”
Section: Recent Evidence For Expanded Indications Of Esd For Egcmentioning
confidence: 99%
“…Jee et al [105] reviewed 129 gastrectomies indicated for extended indication of endoscopic resection and they reported that there was lymph node metastasis in two patients (4%). An et al [106] reported 1.7% of lymph node metastasis even in submucosal cancer (sm1, less than 500 μm) less than 2 cm.…”
Section: Endoscopic Surgery For Gastric Cancermentioning
confidence: 99%